A Simulation Approach for Depletion and Enhancement Mode in β-Ga2O3 MOSFET. Issue 6 (2nd November 2022) - Kachhawa, Pharyanshu; Chaturvedi, Nidhi
Abstract : This paper reports on TCAD simulation of beta-gallium oxide (β-Ga2 O3 ) MOSFET with the channel recessed into a 1-µm thick Si-doped (1 × 10 18 cm −3 ) epitaxial layer. We optimized gate recess thickness to achieve both depletion mode (D-mode) and enhancement mode (E-mode) operations. The simulated β-Ga2 O3 MOSFET structures show optimum D-mode and E-mode characteristics for 150-nm and 15-nm active channel thicknesses, respectively. A comparative study is also done to analyze the thermal and electrical effects by simulating the heteroepitaxial β-Ga2 O3 layer on sapphire substrate [201] and homoepitaxial β-Ga2 O3 layer on β-Ga2 O3 [010] substrate. The MOSFET devices based on the β-Ga2 O3 layers on sapphire substrates show improved performance compared to the devices based on the β-Ga2 O3 layers on β-Ga2 O3 substrates in terms of drain current, transconductance, and breakdown voltage. β-Ga2 O3 epitaxial layers on sapphire substrates exhibit a drain current density of 425 mA/mm with a peak transconductance of 12.2 mS/mm for D-mode operation and 153 mA/mm drain current density with a peak transconductance of 20.8 mS/mm for E-mode operation. In contrast, the MOSFET devices based on the β-Ga2 O3 epitaxial layers on β-Ga2 O3 substrates show a drain current density of 415 mA/mm for D-mode operation and 144 mA/mm drain current density with 3.2 mS/mm peak transconductance for E-mode operation. The MOSFET devices based on the β-Ga2 O3 epitaxial structures on sapphire and β-Ga2 O3 substrates show reliable switching properties with improved subthreshold slope and high Ion /Ioff ratio of 10 11 . These simulation results show potential of laterally scaled β-Ga2 O3 MOSFETs for power-switching applications.